Pengaruh Pupuk Kompos Kulit Buah Kakao Dan Pupuk Tablet Terhadap Produksi Kakao (Theobroma cacao L.) - Muhamad Eza Suprapto; Santi Rosniawaty; Mira Ariyanti (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Cocoa is one of the estate crop whose role is quite important for the national economy, particularly as a provider of employment,  income and foreign exchange. The high export opportunities of cocoa beans has not been followed by the production of cocoa beans in Indonesian. The production of dried cacao  beans in Indonesia is still low. The low productivity of seeds generally caused by  Cherelle wilt of cacao. Wilting occurs due to inability of the cherelle to compete with the other cherelle in absorbing nutrients. Fertilization is an effort to maintain and fulfill the nutrients in the plants. This research is aimed to assess the effect of fertilization using cocoa pod husk and NPK tablets fertilization on cocoa crop yields. This experiment was conducted at PT. PP. Bajabang Indonesia, Cipeundeuy, West Bandung regency from December 2016 to March 2017. The experiment was conducted using a Simple Randomized Block Design that consists 10 treatments: control, single N, P, K fertilizer  297 g/tree, cocoa pod husk  9 kg/tree, cocoa pod husk  9 kg/tree + single N, P, K fertilizer 297 g/tree, cocoa pod husk 18 kg/tree + single N, P, K fertilizer  297 g/tree, cocoa pod husk 9 kg/tree  + NPK tablet fertilizer 20 tablets/tree, NPK tablet fertilizer 20 tablets/tree,  cocoa pod husk  9 kg/tree  +  NPK tablet fertilizer 10 tablets/tree, cocoa pod husk 18 kg/tree + NPK tablet fertilizer 20 tablets/ tree, cocoa pod husk 18 kg/ tree + NPK tablet fertilizer 10 tablets/tree. The result of experiment showed that there was an influence of cocoa pod husk and NPK tablet fertilizer on cocoa fruit weight at 12 MSP, that is cocoa pod husk 9 kg/tree  +  NPK  tablet fertilizer 20  tablets/tree.  Number of cherelle wilted  at 12 MSP with cocoa pod  husk 9 kg/tree  +  NPK  tablet fertilizer 20  tablets/tree.